DIAGNOSTICS AND STATUS ANALYSIS OF THE INCIDENCE OF MALIGNANT TUMORS OF MAXILLOFACIAL AREA IN POLTAVA REGION, 2014 - N.A. Sokolova; L.I. Voloshina; M.G. Skikevych; O.I. Tarakanova (Ukrainian Medical Stomatological Academy, 2015)
In Ukraine, as elsewhere in the world, the epidemiological situation of cancer remains unfavorable. Malignant neoplasms and malignant tumors of maxillofacial area are the second cause of mortality after cardiovascular diseases. Morbidity, disability and mortality due to cancer, have not only medical, but also a great social and economic importance. The authors have analyzed the incidence of malignant neoplasms of five separate locations (lip, tongue, salivary glands, mucous membrane of the mouth, jaw) according to the International classification of Diseases of Tenth Revision. The main sources of information about patients' cancer were primary medical documents on the incidence of malignant neoplasms. All patients were divided into groups on a number of criteria: localization of process, the stage of the disease; demographics: place of residence, age, sex. The incidence of malignant tumors of maxillofacial localization in Poltava region has been studied on the analysis of the indicators for 100,000 male and female population. Data on the number, sex and age composition of the population of Poltava region have been taken from our publications in digest "Activity of medical institutions of the region by 2014". To obtain the necessary data on patients' cancer treatment all cancer patients have been notified. The patients with malignant tumors of maxillofacial localization have been selected. It has been established that maxillofacial cancer incidence is 2.4% of the total cancer incidence (in 2012 it was 3.3%). During the analysis the following data have been revealed: • men suffer 4.2 times more than women (in 2012 it was 3.2). • it's more often observed in patients at the age of 61 - 70 years (30.3%), 51 - 60 years (26.1%), over 70 years (28.6%) and at the age of 41 - 50 years (11.8%). In most cases malignancies have been observed at the age of 41 to 70 years (68.2%). • the largest observed incidence of cancer localization is the cancer of the oral mucosa, tumors of cheek mucosa, of alveolar process, hard and soft palate and bottom of the mouth. 42 cases have been observed (35.3%). • the share of cases neglected for many years remains within a 35 - 80% in tumors of various localizations. • the largest number of neglected cases has been observed in malignant tumors of the tongue - 78.1% (was 60%) and of oral mucous membranes - 76.2% (was 54.5%). The data presented in the article clearly show the following:  the need of continuous studying of malignant tumors of maxillofacial area in the population and the necessity of providing specialized care with mandatory data analysis of considered indicators of early diagnosis of cancer as one of the main criteria for evaluation of dental services.